EFEKTIVITAS PENGELOLAAN ANGGARAN DANA DESA: PADA PERSPEKTIF AKUNTABILITAS, PARTISIPASI, DAN KEPERCAYAAN MASYARAKAT - Fahmi, Muhammad; Yuliani, Yuliani; Fadilah, Neti Rosiana; Lidiana, Lidiana (POLITEKNIK LP3I JAKARTA, 2026)
This study aims to empirically examine the influence of community participation, community trust, and village apparatus accountability on the effectiveness of village fund management. Using a quantitative approach with a causal associative method, data were collected from 98 respondents in Kuin Besar Village and Kuin Kecil Village, Banjar Regency, through a proportionate stratified random sampling technique. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS). The results show that both partially and simultaneously, the three independent variables have a positive and significant effect on the effectiveness of village fund management. Village apparatus accountability was found to be the variable with the most dominant influence, confirming Agency Theory in minimizing information asymmetry. Collectively, the contribution of participation, trust, and accountability to the variance in village fund management effectiveness is 68.4%. These findings confirm that the effectiveness of the budget not only depends on an accountable administrative system but also requires active citizen involvement and a strong moral relationship between the village government and the community. It is recommended that the village government enhance the digitalization of accountability and strengthen integrity through an integrity pact to maintain public trust.